Status of neurodevelopmental impairments among children using rapid neurodevelopmental assessment attending a tertiary care hospital - Uddin, Mohammad Zahir; Rahman, Muhammad Mizanur; Fatema, Kanij; Khan, ARM Sakhawat Hossain; Hossain, Mohammad Monir; Saad, Tania (International Journal of Contemporary Pediatrics, 2019)
Background: Developmental and childhood neuropsychiatric disorders have a large burden throughout the world, including the developing countries. Many children with clinically identifiable developmental problems present late for medical help due to lack of simple measures for their early recognition. These missed opportunities increase the level of dependence and disability of an individual and decrease the productivity of the community at large. So simple measures are needed to determine NDIs at an early age where professional expertise is sparse. Authors objective was to estimate the proportion of children having NDIs in a tertiary care hospital, and to estimate the specific types of NDIs, and their grades of severity, within the study population. Methods: It was a cross sectional study conducted at the Department of Pediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh and the duration of the study was six months. Children aged 0-2 years who were attending Pediatric OPD were included in the study. Sample was collected by lottery method and who fulfilled the inclusion criteria. A two-stage design was followed for detection of NDIs. Stage I was consisted of screening of all children in the sample by Development Screening Questionnaire (DSQ). Stage II consisted of neurodevelopmental assessment using a validated RNDA method of evaluation of all children with DSQ positive screening result. Results: 7.26% children were found to have DSQ positive for NDIs. Cognition and speech was the mostly affected domain. By RNDA, NDIs were found in all DSQ positive cases. Severe impairment was 35.29% of the affected children in speech by RNDA. Detection of NDIs was more in gross motor (52.94% vs 35.29%), fine motor (94.18% vs 17.65%), speech (76.47% vs 64.71%), cognition (94.18% vs 64.71%), behavior (58.82% vs 5.89%) respectively by RNDA than the DSQ. Conclusions: The frequency of NDIs is 7.26% of all children. In certain developmental domain (i.e. gross motor, fine motor, cognition, speech, behavior) RNDA is more effective than DSQ as found in the small-scale study.